2014
DOI: 10.1016/j.jeurceramsoc.2014.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the deposition mechanisms in suspension plasma spray (SPS) and solution precursor plasma spray (SPPS) deposition of yttria-stabilised zirconia (YSZ)

Abstract: Thermal spraying using liquid feedstock has emerged as a promising technology for the deposition of finely structured ceramic coatings. In order to provide a comparative assessment of the deposition mechanisms occurring when spraying suspension or solution feedstock, suspensions of 300 nm-sized ZrO2–4.5 mol.% Y2O3 particles dispersed in water and in ethanol and solutions of zirconium and yttrium salts, corresponding to ZrO2–4.5 mol.% Y2O3 and ZrO2–8 mol.% Y2O3 stoichiometries, were processed by plasma spraying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 63 publications
1
30
0
3
Order By: Relevance
“…SPS is an emerging thermal spray process in which the powder feedstock is replaced by a suspension feedstock. An important benefit of SPS process is the possibility of spraying very fine, poor flowability powders [3,[19][20][21][22][23]. Moreover, the SPS technique would be very favourable to avoid undesirable oxidation of the sealing material because a lot of the plasma energy is destined to solvent (water) evaporation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SPS is an emerging thermal spray process in which the powder feedstock is replaced by a suspension feedstock. An important benefit of SPS process is the possibility of spraying very fine, poor flowability powders [3,[19][20][21][22][23]. Moreover, the SPS technique would be very favourable to avoid undesirable oxidation of the sealing material because a lot of the plasma energy is destined to solvent (water) evaporation.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the SPS technique would be very favourable to avoid undesirable oxidation of the sealing material because a lot of the plasma energy is destined to solvent (water) evaporation. However, limiting energy during plasma deposition can compromise coating microstructure and adherence since the particles may not melt as much as required [3,19,21]. For this reason, the optimisation of solid content and stability of SPS feedstock containing SiC particles is necessary to obtain coatings in which the amount of SiC particles can be maximised.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have demonstrated that nanometric ZrO 2 [17,18], TiO 2 [19][20][21] and Al 2 O 3 [22,23] are successfully deposited by SPS. The SPS coatings obtained using nanopowder feedstock exhibit superior characteristics due to the fact that they present a much lower porosity, leading to a denser structure.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it may be a magnetron spu ering [13,14], plasma spraying [15][16][17][18][19][20], which consists in creating a plasma of high temperature, to 2000 K, and then delivered thereto, by a carrier gas, the material in the form of a powder that will be deposited. Hass et al [15] concluded that a ceramic coating obtained this way may exhibit less consistency with the substrate and be characterized by higher porosity and non-uniform distribution of the pore volume fraction and shape.…”
Section: Synthesis Of Nanometric Zirconia In the Vapor Phasementioning
confidence: 99%